2018
DOI: 10.1080/10826084.2018.1441309
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors that Shape Substance Abuse and Related Mental Health of Women Military Veterans who Use Community-Based Services

Abstract: Findings can inform interventions and services that ameliorate vulnerability to substance abuse and other health risks among women Veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Women veterans report their transition out of the military to be hard and isolating, an experience that is made more challenging by substance abuse, fractured personal relationships, unemployment and homelessness, and an unstructured daily life (Derefinko et al, 2018; Evans, Glover, et al, 2018). In the present study, we found that the burden of finding and receiving VA health care is placed on women veterans’ shoulders, not borne by the system itself, which can be an additional stressor in the lives of women veterans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women veterans report their transition out of the military to be hard and isolating, an experience that is made more challenging by substance abuse, fractured personal relationships, unemployment and homelessness, and an unstructured daily life (Derefinko et al, 2018; Evans, Glover, et al, 2018). In the present study, we found that the burden of finding and receiving VA health care is placed on women veterans’ shoulders, not borne by the system itself, which can be an additional stressor in the lives of women veterans.…”
Section: Discussionmentioning
confidence: 99%
“…This model conceptualizes health services utilization as a function of both individual characteristics and external contexts (e.g., health care system, societal norms). In our previous work, we examined how health care utilization by women veterans is shaped by their individual psychosocial characteristics, including the need for care, predisposing factors, and personal experiences (Evans, Glover, Washington, & Hamilton, 2018). In the present article, we focus on whether and how women veterans' use of VA care is affected by contextual factors, for example, women's prior experiences of accessing VA care, and VA organizational characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, women who have experienced trauma or who have posttraumatic stress disorder (PTSD) are at an elevated risk for developing AUD [6]. When asked about factors relating to their substance use, women veterans frequently cited childhood trauma, as well as military sexual assault and harassment [7]. Similar to the general population of incarcerated women, 36% of incarcerated women veterans self-reported having an AUD during an in-person visit with outreach staff who work in prisons [8], and 41% of women veterans who received outreach while in jail or court were diagnosed with AUD within a year of that outreach [9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Black adults are less likely to be prescribed opioids (Burgess et al, 2014) or monitored by a pain specialist (Hausmann et al, 2013). Furthermore, untreated physical pain is a critical reason why women veterans initiate illicit use of opioids and other substances (Evans et al, 2018). Therefore, Black women veterans may have significant unmet needs for pain relief services, which could elevate their risk for opioid and other substance use disorders.…”
Section: Discussionmentioning
confidence: 99%